2007
DOI: 10.1002/ajmg.b.30550
|View full text |Cite
|
Sign up to set email alerts
|

A subgroup of Tourette's patients overexpress specific natural killer cell genes in blood: A preliminary report

Abstract: Gilles de la Tourette Syndrome (TS) is a heritable, neurodevelopmental disorder characterized by motor and vocal tics. As no single gene or region has emerged from standard linkage approaches, TS may result from several as-yet-unidentified genetic factors, and may also occur due to infection-triggered, autoimmune processes. Etiological or pathogenic differences might result in clinically indistinguishable TS subgroups. We have previously used whole genome human oligonucleotide microarrays in an attempt to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 51 publications
5
43
1
Order By: Relevance
“…As in the previous study (Lit et al, 2007), these genes showed increased expression for TS compared to NC (Figure 6; Table 4). A genes (Pearson correlation, p ≥ 0.95)-by-samples (smooth correlation, p ≥ 0.95) unsupervised cluster using these 7 probes demonstrates good separation of TS from NC ( Figure 7A).…”
Section: Presence Of Previously Identified Genessupporting
confidence: 83%
See 4 more Smart Citations
“…As in the previous study (Lit et al, 2007), these genes showed increased expression for TS compared to NC (Figure 6; Table 4). A genes (Pearson correlation, p ≥ 0.95)-by-samples (smooth correlation, p ≥ 0.95) unsupervised cluster using these 7 probes demonstrates good separation of TS from NC ( Figure 7A).…”
Section: Presence Of Previously Identified Genessupporting
confidence: 83%
“…Expression of 7 probes, representing 6 genes analogous to those previously found differentially expressed in TS compared to controls (Lit et al, 2007), was also significantly different in this study between TS and NC for the 10-12 age group (Table 4). As in the previous study (Lit et al, 2007), these genes showed increased expression for TS compared to NC (Figure 6; Table 4).…”
Section: Presence Of Previously Identified Genessupporting
confidence: 60%
See 3 more Smart Citations